Um estudo sobre o abuso sexual de crianças e adolescentes acompanhadas no Centro de Referência Especializado de Atendimento a Mulher–CREAM/Centro de Referência Especializado de Assistência Social – CREAS em Abaetetuba-PA - SILVA, Jessica Dias da (2023)
This work addresses the demands of children and adolescents who have experienced sexual abuse and are in family and/or individual follow-up at the Specialized Referral Center for Women's Care-CREAM/Specialized Reference Center for Social Assistance-CREAS, in the municipality of Abaetetuba-For. For the purpose of apprehending this object, the goal was to understand the determinants involved in this aggression, in order to identify the most susceptible age group; the environment that most victimizes these subjects and to verify which their main violators. The methodological approach adopted was the bibliographical and documentary research, of a qualitative and quantitative nature, with the use of previously structured data collection forms. Thus, the research pointed out that the phase most prone to sexual abuse occurred in childhood and, especially, in the family environment, being the aggression perpetrated by persons of trust of this child or adolescent. Therefore, this violation requires a closer look, which would tend to the professionals' work in a joint articulation with other sectors that give support to these victims and their families, being essential that the social-assistance network works in fact, since only a front of sensitization and effectiveness of rights does not guarantee a resolutive and quality work, understanding that the diverse determinants in the familiar envelope need of a joint and continuous work.